2012
DOI: 10.1021/la3014392
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Electrostatic Charge Transfer by the Electrophoresis of a Charged Droplet in a Dielectric Liquid

Abstract: We have experimentally investigated the electrostatic charging of a water droplet on an electrified electrode surface to explain the detailed inductive charging processes and use them for the detection of droplet position in a lab-on-a-chip system. The periodic bouncing motion of a droplet between two planar electrodes has been examined by using a high-resolution electrometer and an image analysis method. We have found that this charging process consists of three steps. The first step is inductive charge accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 22 publications
8
80
0
Order By: Relevance
“…Analysis of the recorded video to determine the corresponding acquired charge (by balancing the electrostatic force versus the drag force) indicates that the metal ball typically receives about 70 pC to 250 pC of charge from either electrode depending on the applied field strength, while the droplet receives approximately 110 and 200 pC from the negatively and positively charged electrode respectively. The overall behavior of the droplets and metal balls, including the magnitude of charge acquired, is broadly consistent with previous studies [9,14,18,19,24]. Examination of 50-nm thick electrodes after electrically bouncing a water droplet reveals no changes visible to the naked eye.…”
supporting
confidence: 88%
“…Analysis of the recorded video to determine the corresponding acquired charge (by balancing the electrostatic force versus the drag force) indicates that the metal ball typically receives about 70 pC to 250 pC of charge from either electrode depending on the applied field strength, while the droplet receives approximately 110 and 200 pC from the negatively and positively charged electrode respectively. The overall behavior of the droplets and metal balls, including the magnitude of charge acquired, is broadly consistent with previous studies [9,14,18,19,24]. Examination of 50-nm thick electrodes after electrically bouncing a water droplet reveals no changes visible to the naked eye.…”
supporting
confidence: 88%
“…As several other research groups before, we observed that water droplets clearly undergo discharging and re-charging with opposite polarity when making contact with a biased electrode (Hase et al, 2006;Im et al, 2012;Im et al, 2011a;Jalaal et al, 2010;Jung et al, 2008;Lee et al, 2012;Takinoue et al, 2010;Vajdi Hokmabad et al, 2012). We also observed that the initially horizontally centred oil core appears to be moving in the opposite direction of the water shell, when an electric field is applied, regardless of field direction, illustrated in Figure 1b.…”
Section: Deflection Of the Oil Core Against The Direction Of Motion Isupporting
confidence: 80%
“…For example, for a droplet radius ratio (R core /R shell ) of 0.40, the initial velocity is typically of the order of 10 -3 ms -1 , whereas the velocity after first contact is typically of the order of 10 -2 ms -1 . This general behaviour of an initial charge followed by active charging has been observed by other groups (Bailes et al, 2000;Hase et al, 2006;Im et al, 2012;Im et al, 2011a;Jalaal et al, 2010;Jung et al, 2008), although so far no other group has attempted experiments with complex-multiple droplets. As the core-shell droplet was detached from the microcapillary the inner oil droplet was horizontally centred inside the water shell (Fig.…”
Section: General Behaviour Of (O/w)/o Dropletssupporting
confidence: 75%
“…However, the manner in which the charge can be calculated heavily depends on the hydrodynamic drag force coefficients (Ladenburg, Hadamard−Rybczynski, etc.) considered and can differ by as much as 33% [85]. This will be discussed in more detail in the Methodology chapter.…”
Section: Electrophoresismentioning
confidence: 99%